Construction of Hierarchical Surface on Carbon Fiber Paper for Lithium Metal Batteries with Superior Stability. Issue 9 (15th January 2023) - Lee, Youn‐Ki; Cho, Ki‐Yeop; Lee, Sora; Choi, Jiho; Lee, Gwanwon; Joh, Han‐Ik; Eom, KwangSup; Lee, Sungho
Abstract: Lithium is perceived as an ideal anode for next generation batteries with high‐energy density. However, the critical issue of the intractable growth of Li dendrites, which leads to a poor cycling life, still remains. Herein, a hierarchical surface is designed and constructed on carbon fiber (CF) using binders in fabricated CF paper (CFP). The lightweight CF with high mechanical properties is facilitated to establish a 3D network structure as an alternative to Cu foil. The binders are transformed into oxygen‐containing amorphous carbon and sodium carbonate (Na2 CO3 ) using a low‐temperature carbonization process, leading to uniform Li nucleation and a stable solid electrolyte interphase layer with inorganic components. In the electrochemical test, the CFP with amorphous carbon and Na2 CO3 (ANCFP) shows a low Li nucleation overpotential and smooth dendrite‐free Li plating. Furthermore, the ANCFP electrode exhibits good cycling stability in half and symmetrical cells. A full‐cell assembled using a LiFePO4 cathode with high loading (≈13 mg cm −2 ) achieves a high‐energy density of 428 Wh kg −1 (at 0.1 C) and an excellent capacity retention of 85% at 1 C after 300 cycles. This strategy is expected to help realize highly stable Li metal anodes for practical application by suppressing Li dendrite growth. Abstract : A highly tenacious carbon fiber paper (CFP) anode is achieved through facile thermal treatment which leads to the transformation of binders into oxygen‐containing amorphous carbon and sodium carbonate. The surface‐modified CFP facilitates uniform and stable Li plating/stripping during charge–discharge cycling. The lightweight CFP is expected to help the design of lithium metal batteries with high‐energy density.